2011
DOI: 10.1177/0269216311419885
|View full text |Cite
|
Sign up to set email alerts
|

Paramedics experiences and expectations concerning advance directives: A prospective, questionnaire-based, bi-centre study

Abstract: Background The right to self-determination is a fundamental human right and is recognized in several national constitutions (e.g. German Constitution: Article 1, Section 1, Part 1), as is the guarantee of human dignity and the right to physical integrity. 1 For this, 'informed consent' between the patient and health care providers is essential. Discussions and questionnaire-based

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 23 publications
3
54
0
16
Order By: Relevance
“…Surveys of EMS staff may elicit important information and perspectives, which can then be addressed as part of an improvement effort. 32,39,57,58 …”
Section: Needs Assessment Part 1-define the Problemmentioning
confidence: 99%
“…Surveys of EMS staff may elicit important information and perspectives, which can then be addressed as part of an improvement effort. 32,39,57,58 …”
Section: Needs Assessment Part 1-define the Problemmentioning
confidence: 99%
“…Increasingly, palliative care is being recognised as an important skill for emergency care providers more broadly (2)(3)(4)(5)(6), and the perspectives of Australian emergency department (ED) staff in providing palliative care have recently been explored (7)(8). Research focused on pre-hospital emergency care providers is limited and mostly deals with end-of-life issues (9)(10)(11) including moral and legal issues related to withholding resuscitation (12)(13) and advance or present directives (14)(15). One study, using a focus group methodology, explored Australian paramedics' knowledge and attitudes related to the care of patients requiring palliative care (15).…”
Section: Introductionmentioning
confidence: 99%
“…The participants listed several reasons for considering stopping resuscitation such as when it is not likely to be useful to the patient's outcome, prolonged duration of resuscitation when the patient or the legal guardians' preference is against it and in case of advanced terminal illness. Other investigators[ 6 7 ] have highlighted advanced directives as a key factor in resuscitation decisions. In Lebanon, advanced directives are not commonly practiced, partly because they may be at odds with religious beliefs, and partly since the Lebanese society is collectivist, with major life and death decisions made by the family rather than the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the West suggested that prehospital providers prefer withholding resuscitation in cases of futile situations, end-of-life situations, or in the presence of advance directives. [ 6 7 ] Yet deciding to stop resuscitation is challenging to prehospital providers, as this may be beyond their scope of practice. [ 8 ] Online medical control or having prehospital providers consult with an emergency physician for cases where they believe resuscitation to be futile can be helpful.…”
Section: Introductionmentioning
confidence: 99%